2009
DOI: 10.2460/javma.234.6.771
|View full text |Cite
|
Sign up to set email alerts
|

Signalment, history, and outcome of cats with gastrointestinal tract intussusception: 20 cases (1986–2000)

Abstract: Results suggested that in cats, intussusception has a bimodal age distribution, is most commonly jejuno-jejunal, often requires surgical resection and anastomosis, is often associated with alimentary lymphoma or inflammatory bowel disease in older cats, and is readily diagnosed by means of ultrasonography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(71 citation statements)
references
References 31 publications
5
66
0
Order By: Relevance
“…On the contrary, jejuno-jejunal intussusception was found as the most common type of feline gastrointestinal intussusception in another study [10]. In the present case, intussusception was centrally located on the jejunum.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…On the contrary, jejuno-jejunal intussusception was found as the most common type of feline gastrointestinal intussusception in another study [10]. In the present case, intussusception was centrally located on the jejunum.…”
Section: Discussionmentioning
confidence: 49%
“…Recurrence, ileus, intestinal obstruction, intestinal strangulation, and peritonitis are possible complications following surgery [6,10,14,16]. Fortunately, no other complications were identified at 4 months post-surgery in the mentioned case.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Discussion Intussusceptions are defined as a telescoping of one portion of the intestines (intussusceptum) into other portions of the intestinal tract (intusscepiens) (Levitt and Bauer, 1992). Reported causes of intussusceptions in various species include gastrointestinal parasites, gastroenteritis of various etiologies, intestinal masses or neoplasms, abdominal surgery, and may also be idiopathic (Applewhite et al, 2001;Burkitt et al, 2009). The underlyling cause for the intussuception was not identified in the case reported in this manuscript.…”
Section: Introductionmentioning
confidence: 72%
“…Thus, it is uncertain why intussusceptions are not encountered more frequently in Crohn's disease. Regarding cats, Burkitt et al (2009) showed that older cats with intussusception may be more likely to have alimentary lymphoma or inflammatory bowel disease.…”
Section: Oliveira-barros Et Al (2009) Have Recently Suggested a Relamentioning
confidence: 99%